Pengaruh Konseling Menggunakan Strategi Konselin Berimbang Keluarga Berencana (SKB KB) Terhadap Perilaku Ibu dalam Memilih Kontrasepsi di Puskesmas Pembantu Kuala Keritang Tahun 2022 - Mariana, Silvia; Haryanti, Dwi; Ningsih, Nisa Kartika; Gustinainah, Gustinainah (Universitas Batanghari Jambi, 2024)
Indonesia is one of the developing countries in the world. What is often encountered in a developing country is a very large population. Family planning is an effort made by humans to intentionally regulate pregnancy in the family not against the law and Pancasila morals for family welfare. Through the family planning program there will be control over population growth so as to increase the level of health and welfare for families.This study aims to determine the effect of counseling using Balanced Family Planning Counseling Strategies (SKB KB) on the mother's behavior (knowledge, attitude and motivation of the mother) in choosing contraception.The type and research design used in this study was a pre-experimental study with a non-equivalent pretest and posttest one group design. The population in this study were all women of childbearing age aged 15-49 years at the Kuala Keritang Assistant Health Center. The sample size in this study used the Lameshow formula as many as 42 respondents at the Kuala Keritang Assistant Health Center, the sampling technique used in this study was Accidental Sampling. Data was collected using a questionnaire and data processing using the SPSS program. Data analysis in this study was univariate and bivariate analysis using the paired t test statistical test. The results showed that there was an effect of counseling using Balanced Family Planning Counseling Strategy (SKB KB) on mother's knowledge (p = 0.000), mother's attitude (p = 0.000), and mother's motivation (p = 0.000) in choosing contraception.